Disclosure of Transparency, Accountability and Value for Money Concept in Public Sector Financial Management: A Systematic Literature Review - Andi Aliyyah Ramadhani Sam; Haliah Haliah; Andi Kusumawati (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to examine the implementation of transparency, accountability, and the concept of value for money in public sector financial management. The method used is a Systematic Literature Review (SLR), selecting relevant articles from the Scopus database published, the research identifies these principles as crucial in enhancing efficiency, effectiveness, and public trust. The results indicate that transparency and accountability play a crucial role in improving public financial governance and significantly contribute to enhanced financial management efficiency and public trust. The concept of value for money, focusing on efficiency, economy, and effectiveness, is essential in ensuring that each budget expenditure provides maximum benefits and proves beneficial in optimizing budget use. However, challenges such as a lack of information transparency, public involvement, and regulatory constraints remain obstacles to its implementation. Therefore, improving the quality of financial information systems and strengthening human resources capacity are essential for achieving better public financial management and enhancing public service quality.